A quick, easy, cheap, effective, rugged, and safe sample pretreatment and liquid chromatography with tandem mass spectrometry method for the simultaneous quantification of 33 mycotoxins in Lentinula edodes. Issue 15 (August 2014) - Han, Zheng; Feng, Zhihong; Shi, Wen; Zhao, Zhihui; Wu, Yongjiang; Wu, Aibo
<x xml:space="preserve">Abstract</x> Lentinula edodes is one of the most cultivated edible fungi in the world and mycotoxins contamination on it is still little known, although it could be easily attacked by molds in nature. A straightforward LC‐MS/MS method based on a quick, easy, cheap, effective, rugged and safe (QuEChERS) sample pretreatment was proposed and further developed for simultaneous determination of 33 mycotoxins in Lentinula edodes for the first time. The results indicated that the edible macro‐fungi could be infected by the mycotoxingenic fungi, especially Fusarium species leading to some important mycotoxins, i.e., fumonisin B1, fumonisin B2, mycophenolic acid and deoxynivalenol, related health risks generated. Continuous monitoring by the newly developed method is considered to be of interest to confirm the current contamination and further address changes in occurrence revealing the production patterns and responses to circumstance elements of major contaminated mycotoxins to ensure the safer consumption of Lentinula edodes as vegetable and supplementary food. J. Sep. Sci. 2014, 37 (15), 1957–1966) DOI: 10.1002/jssc.201400329 <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Novel devices for solvent delivery and temperature programming designed for capillary liquid chromatography Lincoln Figueira Marins Coutinho, Carlos Eduardo Domingues Nazario, Alessandra Maffei Monteiro, and Fernando Mauro Lanças J. Sep. Sci. 2014, 37 (15), 1903–1910) DOI: 10.1002/jssc.201301324 A syringe‐type pump (175 mm × 120 mm × 391 mm) was newly developed to deliver solvents without flow splitters at maximum pressures up to 350 bar (5000 psi). The pulseless and splitless pumping system operates at a reproducible and accurate flow rate in the nano‐ and micro‐flows ranges. The use of the developed miniaturized liquid chromatography is a good strategy to save mobile phases, reduce the analysis time and improve the peak shape and sensitivity without the use of a mobile phase gradient. Statins and tetracyclines could be successfully separated by TP‐cLC and the analysis time was shorter in comparison to the experiment carried out under isothermal conditions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>